Analisis Faktor-Faktor Yang Mempengaruhi Penerimaan Pph Pasal 21 Badan Padakantor Pelayanan Pajak Pratama Binjai - Illal Nurhabibah; Eka Nurmalasari; Widia Astuty (Jurnal Riset AKuntansi dan Bisnis, 2021)
The type of data used in this study is secondary data and time series data. This study uses data from the past five years, namely the period 2014-2019 obtained from Badan Pusat Statistik (BPS) of Binjai City and KPP Pratama Kota Binjai. Data were analyzed using multiple linear regression models. The results of the study show that: (1) The amount of tax with holding has a negative effect and not signicant the income of PPh Article 21. (2) Gross Regional Domestic Product (GRDP) has a positive effect and significant on the receipt of PPh Article 21 Agency. (3) The number of Population has a positive effect and significant on the receipt of PPh article 21 Agency. (4) The number of the Work Force has a negative effect and significant on the receipt of PPh Article 21 Agency. (5) The amount of Tax Withholding, Gross Regional Domestc Product (GRDP), The number of population, and the number of the Work Force simultaneously affect on the receipt of PPh Article 21 Agency.